Increased maritime activity in the Arctic Risks and possible environmental consequences. - Rweileh, Adham Abu; Irveby Sporgelin, Karl (My University, 2019)
Due to a warming climate, the sea ice is melting in the Arctic, which grants easier access to shipping routes through the Arctic in the summer months. Shipping companies are looking to benefit from these shorter routes and the purpose in this project is to investigate the implications an increased maritime activity can have on the Arctic environment. Using literature review, different aspects are evaluated such as what makes the Arctic special. As a result of the shrinking sea ice extent, the Arctic may face environmental consequences due to the potential increase of maritime activity. Pollution from ships is therefore a vital part of this report as well as how current and future ship regulations helps to reduce the environmental impact on the Arctic region. Results show that an increased marine traffic could have a harmful effect locally. Albedo is a major factor when it comes to the melting of the ice sheets. Light absorbing particles, such as black carbon, accelerate the ice melting process which exposes more ocean water. In contrast to the ice and snow, sea water is much darker which makes it absorb more heat from solar radiation. The Polar Code offers guidelines for operating in the Arctic and the IMO is currently working on an HFO ban in the Arctic. This ban could help the region since the added difficulty of navigating in Arctic waters increase the risk of accidents which may result in oil spills.
Keywords: shipping; arctic; sea ice; environment; climate; black carbon; emissions; pollution; hfo